2006
DOI: 10.1039/b600384b
|View full text |Cite
|
Sign up to set email alerts
|

Surface photochemistry: benzophenone as a probe for the study of silica and reversed-phase silica surfaces

Abstract: This work reports the use of benzophenone, a very well characterized probe, to study new hosts: two reversed-phase silicas. Laser-induced room temperature luminescence of argon purged solid powdered samples of benzophenone adsorbed onto the two different reversed-phase silicas, RP-18 and RP-8, revealed the existence of a low energy emission band in contrast with the benzophenone adsorbed on 60 Å pore silica, where only triplet benzophenone emits. This low energy emission band was identified as the fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…34,35 Note that it was reported that Bzp in triplet states could subtract H-atom from the reverse phased silica and form diphenyl ketyl radical with emission maxima around 575 nm. 36 However, the lack of observation of emission centered around 575 nm in Bzp:MSN indicates that this radical luminescence is negligible in our experiments.…”
Section: ■ Results and Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…34,35 Note that it was reported that Bzp in triplet states could subtract H-atom from the reverse phased silica and form diphenyl ketyl radical with emission maxima around 575 nm. 36 However, the lack of observation of emission centered around 575 nm in Bzp:MSN indicates that this radical luminescence is negligible in our experiments.…”
Section: ■ Results and Discussioncontrasting
confidence: 61%
“…The τ DF component occurring via the rISC process increases exponentially with temperature, which is the opposite trend to the typical TADF process. This kind of opposite trend of temperature on the PL emission was rarely observed previously in TADF emitters; if the RTP minor contribution also impacts the PL dynamics along with the TADF, this behavior is evident. The environmentally induced phosphorescence properties of Bzp have been used effectively to understand solid mesoporous silica surfaces. , Note that it was reported that Bzp in triplet states could subtract H-atom from the reverse phased silica and form diphenyl ketyl radical with emission maxima around 575 nm . However, the lack of observation of emission centered around 575 nm in Bzp:MSN indicates that this radical luminescence is negligible in our experiments.…”
Section: Resultsmentioning
confidence: 84%
“…Some molecules can be protonated when they are encapsulated in SBMs. The guest forms one or more cationic species depending on the available proton-acceptor groups and the acidity of the encapsulating material. In these systems, intermolecular H-bonds may stabilize the encapsulated guest and increase its fluorescence lifetime.…”
Section: Ensemble Average Time-resolved Studies Of Photoinduced Proce...mentioning
confidence: 99%
“…Other molecules, such as ketones and benzophenone, have been used as probes to characterize new solid supports. , Benzophenone (BZP, Scheme ) is widely used to investigate the acidic character of the environment. , As in the previous composites, BZP that is encapsulated in materials that contain Brønsted or Lewis acid sites [ZSM-5 and aluminophosphate (AlPO 4 ) microporous solid] exhibits protonation processes. , In BZP/AlPO 4 complexes, the luminescence spectra show two bands (440 and 470 nm) that are assigned to the H-bonded and protonated BZP species, respectively. The behavior was compared with that of BZP encapsulated in ZSM-5, a host that is less hydrophilic and polar than AlPO 4 . , When Na + cations are introduced into the ZSM-5 framework, Lewis acid sites are favored.…”
Section: Ensemble Average Time-resolved Studies Of Photoinduced Proce...mentioning
confidence: 99%
“…Otherwise if the photoexcited benzophenone ketyl radical receives a hydrogen radical, it gives rise to the product, diphenylcarbinol. 10 Initially the photoproducts from benzophenone were examined by UV visible spectroscopy. Benzophenone shows an absorption peak at 253 nm in ethanol before the reaction, and after the reaction a new peak appeared at l max 4 300 nm.…”
mentioning
confidence: 99%